Identity and typification of Diploneis ostracodarum, Diploneis budayana and Diploneis praeclara (Bacillariophyta) - Jovanovska, Elena; Buczkó, Krisztina; Ognjanova-Rumenova, Nadja G.; Nakov, Teofil; Levkov, Zlatko (Phytotaxa, 2013)
A lectotype and isolectotype for Navicula budayana Pantocsek = Diploneis budayana (Pantocsek) Hustedt, Navicula ostracodarum Pantocsek = Diploneis ostracodarum (Pantocsek) Jovanovska, Nakov & Levkov and Navicula praeclara Pantocsek = Diploneis praeclara (Pantocsek) Cleve-Euler from Köpecz, Neogene fossil deposits in Romania have been made. Typification for each species was based on Pantocsek’s original images and material deposited at the Hungarian Natural History Museum (BP). Unfortunately, the type slides for Diploneis budayana, D. ostracodarum and D. praeclara were lost or destroyed during the course of World War II. Therefore, authentic material from the type locality Köpecz at BP was used to designate the lectotypes for these three species. Detailed LM and SEM observations have been assigned for each taxon, in order to ascertain the variation in valve morphology. Taxonomic descriptions and comments are made for each species. Typification of taxa described by Pantocsek would potentially affect further stratigraphic, comparative or molecular phylogenetic work not just for Tertiary floras but for Recent floras as well. In particular, studies concerning comparisons of these species between localities, such as Lake Ohrid, will greatly benefit from this work. The outcome of such studies will shed light on the evolutionary and biogeographic history of diatoms in the context of geologic events on the Balkan Peninsula.